Selective activation of interleukin-2/interleukin-15 receptor signaling in tumor microenvironment using paired bispecific antibodies - Camilla Jandus; Walter Ferlin; Sébastien Calloud; Alizée Viandier; Pauline Malinge; Nicolas Fischer; Limin Shang; Krzysztof Masternak; Julien Montorfani; Eric Hatterer; Laurence Chatel; Adeline Lesnier; et al. (Journal for ImmunoTherapy of Cancer)
Background Owing to their roles in promoting T cell and natural killer (NK) cell activation and proliferation, interleukins-2 (IL-2) and interleukins-15 (IL-15) have been pursued as promising pathways to target in cancer immunotherapy. Nonetheless, their wider therapeutic application has been hampered by severe dose-limiting toxicities including systemic cytokine release and organ edema for IL-2, and inconvenient intratumoral administration for IL-15. To address these safety issues, we generated IL-2R/IL-15R×TAA (tumor-associated antigen) bispecific antibody (bsAb) pairs to selectively activate IL-2R signaling in the tumor microenvironment.Methods Each bsAb pair is composed of one bsAb targeting CD122 and a TAA epitope, and the other bsAb targeting CD132 and the same or a different TAA epitope. In vitro assays were performed to characterize the IL-2R/IL-15R agonistic activity of the bsAb pairs, as well as their capacity to enhance T-cell-mediated killing of TAA+ malignant cells. Using a syngeneic mouse tumor model, in vivo biological activity and systemic toxicity of the bsAb pairs were assessed in comparison with IL-2. The in vivo antitumor activity was assessed in combination with an anti-mouse programmed cell death protein 1 (mPD-1) monoclonal antibody.Results We demonstrated with two different TAAs (human epidermal growth factor receptor 2 (HER2) and mesothelin (MSLN)) that the CD122×TAA/CD132×TAA bsAb pairs mediate effective activation of immune cells exclusively in the presence of TAA+ tumor cells. In syngeneic hMSLN-MC38 tumor-bearing mice, the CD122×MSLN-1/CD132×MSLN-2 bsAb pair promotes selective activation and expansion of NK cells and central memory CD8+ T cells inside the tumor without inducing organ edema or systemic cytokine release, two well-known manifestations of IL-2 associated toxicity. In combination with checkpoint inhibitor anti-mPD-1, the bsAb pair boosts the accumulation of CD8+ effector T cells and NK cells, leading to a favorable CD8+ T cell to CD4+ regulatory T cell ratio for a more robust inhibition of tumor growth.Conclusions Overall, the findings suggest that this innovative therapeutic approach effectively leverages the antitumor activity of IL-2 and IL-15 pathways while minimizing their associated systemic toxicities. This dual bsAb format holds potential for broader application in other immune-activating pathways.